Caracterização bioquímica e funcional de uma nova Thrombin-like isolada da peçonha de Bothrops pauloensis - Costa, Fábio Lucas Silva (2008)
Serine proteinases isolated from snake venom have an important role in the formation and dissolution of clots. These toxins primarily, the thrombin-like enzymes affect the hemostatic system resulting in blood incoagulation. At present study, a thrombin-like enzyme named Tl-Bp was isolated from Bothrops pauloensis snake venom and its biochemical, enzymatic and pharmacological characteristics were determined. Tl-Bp is a glycoprotein that contain both carbohydrates N-linked and sialic acid in its structure, has Mr. = 34,000 at reducing conditions and pI ~ 6.4. The N-terminal sequence of the enzyme (VIGGDECDINEHPFL) showed high similarity when compared with other thrombin-like enzymes isolated from snake venoms. Tl-Bp showed high clotting activity upon bovine and human plasma and was inhibited by PMSF, benzamidine and leupeptin. Moreover, showed stability when examined at different temperatures (-70°C to 37°C), pHs (3 to 9) and presence of divalent metal ions (Ca2+, Mg2+, Zn2+ and Mn2+). Tl-Bp showed high catalytic activity upon natural substrates such as fibrinogen and synthetic, such as TAME, S-2238 and S-2288, moreover, showed kallikrein-like activity, but was unable to act upon S-2765 and plasmin substrate. The enzyme did not induce hemorrhage, myotoxicity, edema and platelet aggregation as well as proteolytic activity upon casein. Take together, our data show that Tl-Bp is a new thrombin-like enzyme isoform isolated from Bothrops pauloensis snake venom.